Application of Liquid Chromatography in Food Analysis - Núñez, Oscar; Lucci, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food products are very complex mixtures consisting of naturally occurring compounds and other substances, generally originating from technological processes, agrochemical treatments, or packaging materials. However, food is no longer just a biological necessity for survival. Society demands healthy and safe food, but it is also increasingly interested in other quality attributes more related to the origin of the food, the agricultural production processes used, the presence or not of functional compounds, etc. Improved methods for the determination of authenticity, standardization, and efficacy of nutritional properties in natural food products are required to guarantee their quality and for the growth and regulation of the market. Nowadays, liquid chromatography with ultraviolet detection, or coupled to mass spectrometry and high-resolution mass spectrometry, are among the most powerful techniques to address food safety issues and to guarantee food authenticity in order to prevent fraud. The aim of this book is to gather review articles and original research papers focused on the development of analytical techniques based on liquid chromatography for the analysis of food. This book is comprised of six valuable scientific contributions, including five original research manuscripts and one review article, dealing with the employment of liquid chromatography techniques for the characterization and analysis of feed and food, including fruits, extra virgin olive oils, confectionery oils, sparkling wines and soybeans.